The development of 'Petanque match statistics': an android-based application for petanque matches analysis - Nur Salsabila Rhesa Pandhadha Putra; Muchamad Arif Al Ardha; Nurhasan Nurhasan; Kolektus Oky Ristanto; Sauqi Sawa Bikalawan; Rizki Satrio Utomo; Kukuh Pambuka Putra; James Lin; Resfiana Irani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The accelerated pace of technological advancement necessitates that many disciplines align themselves with these developments, whether directly engaged in the process or not. The field of sports provides an illustrative example of the profound impact of modern technology on various disciplines. This research aimed to develop an Android-based statistical application, designated "Petanque Match Statistic," which was designed to analyze Petanque matches. The research and development (R&D) methodology was employed to undertake six project stages. The application, constructed on the Kodular platform, offers real-time data capture, sophisticated statistical analysis, interactive visualization, and comprehensive performance reporting. The application was subjected to rigorous alpha and beta testing to ensure its accuracy, reliability, and usability. Following its deployment, user training and a support system were established. Continuous evaluation and user feedback facilitated ongoing improvements. The application significantly enhances match analysis, benefiting players, coaches, analysts, and fans by providing accurate, real-time data and comprehensive insights, thereby promoting the growth and development of the sport of petanque.